ABDULLA AVLONI'S VIEWS ON EDUCATION AND ENLIGHTENMENT - Jabbarova Yulduz Jumaniyazovna (Western European Studies, 2026)
The article presents a comprehensive analysis of the pedagogical and enlightenment views of Abdulla Avloni, an outstanding Uzbek thinker, poet, educator, and public figure of the early 20th century. His ideas are examined in the context of the Jadid movement and the socio-cultural transformations in Turkestan. Special attention is given to understanding education as a decisive factor in social progress, the role of moral upbringing, and the significance of schools and teachers in personality formation. Based on an analysis of Avloni's works, his contribution to the development of national pedagogical thought is revealed, and the relevance of his ideas for the modern education system of the Republic of Uzbekistan is determined.
Keywords: Abdulla Avloni; education; enlightenment